Routing for context-addressable messages using Predefined Concept Connection Map in delay tolerant network - Radosław Olgierd Schoeneich (International Journal of Distributed Sensor Networks)
This article presents methods of nodes discovery and message routing for a context-based addressing in Delay and Disruptive Tolerant Networks. The context-based addressing is the novel way of descriptive addressing that is based on ontology model. The context-based addressing enables description of each node by a set of concepts. The main idea of this article is to present the method of the addressees discovery that uses specialized graph composed of concepts. It is called Predefined Concept Connection Map. The Predefined Concept Connection Map describes physical communication abilities between context-based addressed nodes. In this article, ns-2 simulations are presented. They are based on specially designed simulation model which supports context-based address assigned for each Delay and Disruptive Tolerant Network node.